Theoretical study on angular momentum polarization parameters, branching ratios, and anisotropy parameters of chlorine atoms from Photodissociation of Iodine Monochloride. Issue 3 (9th June 2012) - Matsuoka, Takahide; Oonishi, Sayo; Yabushita, Satoshi; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Low‐lying excited state potential energy curves (PECs), nonadiabatic coupling terms, and transition dipole moments of ICl have been obtained by a spin‐orbit configuration interaction method. The angular momentum polarization parameters of photofragments can be calculated from these properties of the molecule. The first‐rank parameter Im[a1(1)(//, ⟂)] of the ground state photofragment Cl(2P3/2) in the first absorption band (490–560 nm) is very sensitive to the PECs of the low‐lying excited states, especially the A(1) and B(0+) states. The phase part of the calculated parameter Im[a1(1)(//, ⟂)] agrees well with experiment. We further clarify the characteristics of avoided crossing between the X(0+) and B(0+) states. We calculated the product fraction of Cl*(2P1/2) and the anisotropy parameter β to demonstrate the effect of photoabsorption caused by the z(1) state, which supports a recent experimental analysis. © 2012 Wiley Periodicals, Inc.